Method of Measuring the Efficiency of the Conversion of Nuclear Energy into Optical Energy. (8th December 2015) - Batyrbekov, Erlan G.; Gordienko, Yuriy N.; Khasenov, Mendykhan U.; Ponkratov, Yuriy V.
Abstract : A method of measuring the efficiency of converting nuclear energy into optical energy was developed based on correlations between intensities of the research line and the nitrogen second positive system in an Ar-N2 mixture. In addition, the values of the coefficient of the conversion of nuclear energy into radiation at the lines of a Hg triplet in mixtures of Хе-Hg and Kr-Hg were determined. The values measured correspond to a selectiveness of pumping of 7 3 S1 that was close to 1 (δ = 0.8 ± 0.2 ).